Enhanced nitrate-to-ammonia electroreduction on manganese-doped ceria with oxygen vacancies - Sun, Xiaoting; Rong, Wanting; Wang, Lanfang; Lv, Jiangnan; Yang, Ruixia; Liang, Tingting; Yang, Qianwen; Xu, Xiaohong; Liu, Yang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
[Display omitted] •We successfully synthesized Mn-CeO2−x nanoparticles, where Mn2+ is stabilized within the CeO2−x host lattice.•Mn-CeO2−x attains the highest NH3 FE of 91.8 % at −0.60 VRHE and the maximum NH3 yield rate of 1.01 mmol h−1 cm−2.•Mn doping optimizes the electronic structure of CeO2−x catalysts, leading to the generation of ample active hydrogen. Electrochemical NO3– reduction reaction (NO3−RR) represents a promising avenue for efficient and sustainable synthesis of ammonia (NH3), with active hydrogen playing a pivotal role in multiple hydrogenation steps. Manganese (Mn)-based electrocatalysts have demonstrated potential in modulating active hydrogen, however, achieving atomically dispersed Mn active sites poses a fundamental challenge. To address the issue, we synthesize Mn-doped ceria with oxygen vacancies (Mn-CeO2−x) nanoparticles, where Mn2+ is stabilized within the CeO2−x host lattice, to facilitate efficient NO3− reduction to NH3. The highest NH3 FE of 91.8 % is observed over Mn-CeO2−x catalyst at −0.60 VRHE and the maximum NH3 yield rate reaches 1.01 mmol h−1 cm−2, outperforming other metal (M = Fe, Co, Ni, and Cu) doped and undoped CeO2−x nanoparticles. Experimental analysis and density functional theory (DFT) calculations cooperatively elucidate that the Mn doping optimizes the electronic structure of CeO2−x catalysts, leading to the generation of ample active hydrogen, improve the reaction kinetics and promote the *NH2O → *NH2OH step in NO3−RR. Our study introduces a rare-earth metal oxide platform for dispersing transition metal active sites, enabling the regulation of active hydrogen and the enhancement of electrocatalytic performance in NO3−RR.